PAPR Analysis of Fifth Generation Multiple Access Waveforms for Advanced Wireless Communication - Mahender, Kommabatla; Anil Kumar, Tipparti; S Ramesh, K (International Journal of Engineering and Technology, 2018)
This paper describes the aspects of multiple access for emerging (5G) Wireless Communication Systems. Orthogonal Frequency Division Multiplexing (OFDM) is best suited for fourth generation (4G) but it suffers from the problem of high Peak to Average Power Ratio (PAPR) & Side band leakage. Single carrier frequency division multiple access (SC-FDMA) has worked like an alternative to OFDMA only in the uplink process and PAPR was reduced. OFDM based 4G network is not capable of supporting diverse applications and these applications can be implemented by 5G.Â  High traffic requirements of 5G can be evaluated by using multiple access schemes, namely filter-bank multi-carrier (FBMC), universal-filtered multi-carrier (UFMC), generalized frequency-division multiplexing (GFDM). Comparison of PAPR reduction is done based on Complementary Cumulative Distribution Function (CCDF), for various multiple access 5G waveforms.Â Â